2019
DOI: 10.3390/ijms20143505
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and Meibomian Gland Dysfunction: Utility of Lipidomics and Experimental Prospects with a Diet-Induced Obesity Mouse Model

Abstract: Meibomian gland dysfunction (MGD) is the leading cause of dry eye disease and loss of ocular surface homeostasis. Increasingly, several observational clinical studies suggest that dyslipidemia (elevated blood cholesterol, triglyceride or lipoprotein levels) can initiate the development of MGD. However, conclusive evidence is lacking, and an experimental approach using a suitable model is necessary to interrogate the relationship between dyslipidemia and MGD. This systematic review discusses current knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 77 publications
(247 reference statements)
2
30
0
Order By: Relevance
“…In recent years, several clinical studies have demonstrated that moderate-to-severe MGD was associated with high total cholesterol and low-density lipoprotein blood levels [85,86]. Thereafter, dyslipidemic animal models were used to study the Meibomian gland and, more specifically, MGD [87][88][89]. To investigate whether systemic lipid disorders can be associated with DED and/or MGD, a study used three transgenic adult mice models, apolipoprotein-E knockout (APOE-KO), low-density lipoprotein receptor knockout (LDLR-KO) and a mouse model with overexpression of human apolipoprotein CIII (ApoCIIIKI), compared to age-and gender-matched C57BL/6 mice [87].…”
Section: Association Between Dyslipidemia and Mgdmentioning
confidence: 99%
“…In recent years, several clinical studies have demonstrated that moderate-to-severe MGD was associated with high total cholesterol and low-density lipoprotein blood levels [85,86]. Thereafter, dyslipidemic animal models were used to study the Meibomian gland and, more specifically, MGD [87][88][89]. To investigate whether systemic lipid disorders can be associated with DED and/or MGD, a study used three transgenic adult mice models, apolipoprotein-E knockout (APOE-KO), low-density lipoprotein receptor knockout (LDLR-KO) and a mouse model with overexpression of human apolipoprotein CIII (ApoCIIIKI), compared to age-and gender-matched C57BL/6 mice [87].…”
Section: Association Between Dyslipidemia and Mgdmentioning
confidence: 99%
“…In the eye, dyslipidemia is also thought to initiate meibomian gland dysfunction (MGD), the leading cause of dry eye disease [ 11 , 12 ]. The meibomian glands are modified sebaceous glands in the eyelids which produce meibum, the tear film lipid component [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the normal lipid composition could also be pro-inflammatory, serving as a potential precursor for blepharitis, which can affect the normal secretory function of the meibomian gland [ 13 , 23 , 24 ]. This can lead to reduced tear film quality and stability and, ultimately, ocular surface inflammation as occurs in MGD and dry eye [ 4 , 11 , 12 , 13 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations